(untitled) (International Journal of Innovative Technologies in Economy, 2021)
The article proposes an ecologically oriented model of integrated management of Ukrainian enterprises based on coimplex integration of environmental aspects into their management system at all stages of the life cycle, which will increase the competitiveness of enterprises and become the basis for their successful transition to sustainable development in the medium term. To restore and increase the life-sustaining conditions of nature on the basis of adequate compensation for damage to ecosystems, the main provisions of the concept of balanced interaction of companies with the environment have been developed. The concept implies adequate compensation for damage to nature by determining the rational relationship between levels of production and resources consumed. Based on the concept, an ecologically oriented model of integrated corporate governance has been created, the main difference from the existing international ISO standards and their analogues is the integration of environmental aspects into the organization’s management system, which allows to take into account the environmental component at all stages of the life cycle. The introduction of an environmentally oriented model of integrated management in the company will ensure effective environmental transformation of the management system, which will serve as a basis for improving the environmental acceptability of their activities.